2005
DOI: 10.1007/s00125-005-1831-2
|View full text |Cite
|
Sign up to set email alerts
|

Oral probiotic administration induces interleukin-10 production and prevents spontaneous autoimmune diabetes in the non-obese diabetic mouse

Abstract: Orally administered VSL#3 prevents autoimmune diabetes and induces immunomodulation by a reduction in insulitis severity. Our results provide a sound rationale for future clinical trials of the primary prevention of type 1 diabetes by oral VSL#3 administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
241
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(248 citation statements)
references
References 58 publications
3
241
0
2
Order By: Relevance
“…Other studies have also reported that probiotics induce IL-10 production. 34,35 Interestingly, mice pretreated with probiotics did not demonstrate an increased IL-10 response to LPS challenge. This may be due to a primary effect of probiotics in preventing an LPS-induced rise in proinflammatory cytokine secretion, or alternatively, a pretreatment with probiotics induces a maximal up-regulation of IL-10.…”
Section: Discussionmentioning
confidence: 97%
“…Other studies have also reported that probiotics induce IL-10 production. 34,35 Interestingly, mice pretreated with probiotics did not demonstrate an increased IL-10 response to LPS challenge. This may be due to a primary effect of probiotics in preventing an LPS-induced rise in proinflammatory cytokine secretion, or alternatively, a pretreatment with probiotics induces a maximal up-regulation of IL-10.…”
Section: Discussionmentioning
confidence: 97%
“…[191][192][193] However, other probiotic strains are capable of ameliorating EAE, 194 and other experimental autoimmune diseases that are known to be Th1 mediated, such as various models of rheumatoid arthritis [195][196][197] or type 1 diabetes. 198 Together, these fi ndings highlight the need for care in choosing appropriate probiotic strains for particular applications. In this process, it needs to be taken into account that the response to probiotic supplementation depends on the immunological status of the host, as demonstrated by in vitro 98,199 and in vivo experiments.…”
Section: Final Comments and Thoughtsmentioning
confidence: 99%
“…Selective decontamination of the gastrointestinal tract may prevent this response in a similar manner in which it prevents translocation of bacteria. Accordingly, we are seeing an increase in investigational efforts involving the use of probiotics [8] to modulate type 1 diabetes. In addition, in the context of antibiotic usage, the identification of unquestionable linkages between an autoimmune disorder, gut flora and antibiotics would add important information to the ongoing debate regarding appropriate versus spurious use of these agents.…”
Section: To the Editormentioning
confidence: 99%